Impact of Collaborative Learning in Higher Education Environment - Soetam Rizky Wicaksono (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
The adoption of collaboration in the learning process is difficult, especially in higher education. Higher education's distinctiveness requires unique approaches to implementing collaborative learning. This study's outcomes are likely to inform collaborative learning case studies in universities. So it can be used without sacrificing learning's aim. In addition, the success rate of collaborative learning can be obtained in a different but still effective approach. This study employed FGD (Focus Group Discussion) to evaluate three positive teaching questions. Based on experiment results, collaborative learning can be successfully applied with numerous key criteria. These aspects include a supportive classroom environment for numerous students, a comparison with other conventional classes, and assignments that encourage small and large group collaboration in phases. The collaborative learning model must be retested empirically to answer the primary research topic. According to interviews and polls, despite student happiness, there are still many flaws that must be fixed on both lecturer and student sides. To enhance collaborative learning, it is suggested to use project-based tasks as addition. Empirical experiments are still needed to validate the statement.